Income, consumption and remittances: Evidence from immigrants to Australia - Giulia Bettin; Riccardo Lucchetti; Alberto Zazzaro (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2009)
For many countries, remittance behaviour by migrants is an important component of their overall international financial flows. To date, the empirical literature has analysed the propensity to remit as a function of migrants' socio-economic characteristics. However, no studies have fully addressed the empirical implications of remittance behaviour being determined in the broader context of migrants' labour, income and consumption allocation strategy. On the contrary, the migrant's income has almost always been treated as exogenous in this context. The aim of this study is to estimate a remittance equation that detects the main determinants of remittance behaviour while addressing endogeneity and reverse causality relationships between remittances, income, consumption and savings. Moreover, since a large share of individuals do not remit money at all, an instrumental variable variant of the double-hurdle selection model is proposed and estimated by LIML. A sending country perspective is adopted in the empirical analysis by considering the first cohort of the Longitudinal Survey of Immigrants to Australia. We find that endogeneity is substantial and that estimates obtained by the methods previously employed in the literature may be very misleading if given a behavioural interpretation. Our results confirm some theoretical predictions and shed light on others; notably, we show that selfish motives in remitters are at least as important as altruistic motives.
Keywords: F24; F22; C21; C24; 330; Double-hurdle model; migration; remittances